2014
DOI: 10.1155/2014/918135
|View full text |Cite
|
Sign up to set email alerts
|

Mild Clinical Course of Severe Fever with Thrombocytopenia Syndrome Virus Infection in an Elderly Japanese Patient

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious and hemorrhagic disease recently described in China and western Japan. A 71-year-old healthy Japanese woman noticed a tick biting her after harvesting in an orchard and removed it herself. She developed diarrhea, anorexia, and chills eight days later. Because these symptoms continued, she visited a primary care physician 6 days after the onset. Laboratory data revealed thrombocytopenia, leukocytopenia, and elevated liver enzymes. She … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 15 publications
(41 reference statements)
0
18
0
Order By: Relevance
“…Although serological assays were available for laboratory diagnosis in some local health laboratories, no case was diagnosed by serological assays in this study. Third, the lack of serological testing may have failed to detect mild cases in our analysis, although a mild case of SFTS has been reported in Japan [ 26 ].…”
Section: Discussionmentioning
confidence: 97%
“…Although serological assays were available for laboratory diagnosis in some local health laboratories, no case was diagnosed by serological assays in this study. Third, the lack of serological testing may have failed to detect mild cases in our analysis, although a mild case of SFTS has been reported in Japan [ 26 ].…”
Section: Discussionmentioning
confidence: 97%
“…Ohagi et al 13 reported a case of platelet specific haemophagocytosis in the bone marrow. Takahashi et al 3 reported an autopsy case with marked erythrophagocytosis in the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have only been nine patients from three reports with a clear description of haemophagocytosis in bone marrow examinations (table 3). Ohagi et al 13 reported one case with mild hypocellular marrow and platelet specific haemophagocytosis in bone marrow aspirates. Takahashi et al 3 reported six cases in Japan, including five fatal cases diagnosed retrospectively and one case diagnosed at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, ribavirin has been used for the SFTS treatment in Korea and abroad [914]. Intravenous ribavirin has some advantages that time to therapeutic effect is relatively faster than oral ribavirin and it can be used for patients who are not allowed to be administered orally.…”
Section: Discussionmentioning
confidence: 99%